Analysis Titer of Epidermal Growth Factor Receptor on Nasopharyngeal Cancer Patients Based on Stadium and Histopathological Profile in Dr. Zainoel Abidin General Hospital Banda Aceh - Benny Kurnia; Fera Kamila Kemal; Basri Abdul Gani (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2021)
Introduction: Nasopharyngeal carcinoma ranks first in incidence at the head and the neck departement. Epidermal Growth Factor Receptor (EGFR) is a transmembrane tyrosine kinase receptor from the ErbB family. Excess EGFR titer is an indication of a malignant transformation and cell differentiation that can ultimately determine the effectiveness of using anti EGFR drugs nasopharyngeal carcinoma patients. Objective: To determine the EGFR titer of nasopharyngeal cancer tissue based on the stage and histopathological profile in Dr. Zainoel Abidin Banda Aceh. Methods: Patients with suspected nasopharyngeal carcinoma were subjected to a nasopharyngeal biopsy examination, some samples were sent to the Anatomical Pathology Laboratory of the General Hospital Dr. Zainoel Abidin Banda Aceh for histopathological examination and some were sent to the Research Laboratory of the Faculty of Dentistry, Syiah Kuala University for examination of EGFR titers. This study was conducted from January 2020 to October 2020. Results: There were 17 samples of nasopharyngeal carcinoma. Based on the results of the Paired T test analysis, it can be seen that there is a difference in the quantity of EGFR titers of each study subject with the variable stage and histopathological profile. Specifically, the Paired T test analysis between EGFR titers and Stadium (P<0.05; 0.00); and analysis of EGFR titer with histopathological profile (P<0.05; 0.00). In general, the Friedmann test analysis showed that there were significant differences in the incidence of nasopharyngeal carcinoma in patients with regard to age, histopathological profile and stage (P<0.05). Conclusion: EGFR titer quantity has a positive relationship with nasopharyngeal carcinoma stage and there is no relationship between EGFR titer and histopathological profile of nasopharyngeal carcinoma